2020
DOI: 10.3390/cancers12082056
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of BRAF Mutation on the Recurrence of Papillary Thyroid Carcinoma: A Meta-Analysis

Abstract: Previous meta-analyses indicated that the BRAF V600E mutation was associated with an increased recurrence rate of papillary thyroid carcinoma (PTC). However, with recent publications of large cohort studies, the need for an updated meta-analysis increases. Therefore, we conducted a comprehensive meta-analysis to assess the impact of the BRAF V600E mutation on PTC recurrences. We performed a literature search using PubMed, SCOPUS, the Cochrane Database of Systematic Reviews, and the Web of Science Core Collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…The most common mutation in TC is the BRAF V600E mutation, which has appeared to be associated with a higher risk of cancer recurrence [ 3 ]. However, this association has recently been disputed [ 4 ]. TERT promoter mutations are associated with distant metastases and a higher risk of mortality in advanced cases of TC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common mutation in TC is the BRAF V600E mutation, which has appeared to be associated with a higher risk of cancer recurrence [ 3 ]. However, this association has recently been disputed [ 4 ]. TERT promoter mutations are associated with distant metastases and a higher risk of mortality in advanced cases of TC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, all patients with hairy cell leukemia (HCL) harbor variants in the BRAF gene [ 25 ]. Approximately 50% patients with melanoma and papillary thyroid carcinoma carry a variant of the BRAF gene [ 26 , 27 ]. On the other hand, approximately 10% of colorectal cancer patients harbor a variant of the BRAF gene [ 28 ].…”
Section: Integrated Interpretation: Tissue Specificity and Environmen...mentioning
confidence: 99%
“…At the same time, Ahn et al and Yan et al presented no correlation between BRAF V600E and any of the PTC features [ 18 , 19 ]. Li et al suggested that the geographical location and tumor stage should be considered when the impact of a BRAF mutation on the cancer outcome is assessed [ 20 ].…”
Section: Genetic Aberrations Markersmentioning
confidence: 99%